T20 resilience and inclusive growth - Kazumasa Iwata; Sébastien Jean; Christian Kastrop; Chris Loewald; Nicolas Véron (Kiel Institute for the World Economy (IfW), 2017)
Severe recessions and financial crises are frequent. Their effect on the economy is persistent and often exceeds initial projections. They can also be a strong driver of widening inequality. Therefore it is important that measures be taken to minimise the risk of such events while strengthening the potential for economies to innovate and prosper (Phelps, Mass Flourishings: How Grassroots Innovation Created Jobs, Challenge and Change, 2013). An economy's resilience to crises and recessions can also be strengthened. Minimising risks requires the accurate monitoring of home-grown vulnerabilities in realtime; coping with the consequences means identifying and putting in place policy settings and mechanisms that can help absorb the impact of a severe downturn and facilitate a swift rebound of economic activity. Strengthening resilience will also provide a key contribution to solving the global problems of rising populism, nationalism and protectionism.
Keywords: A10; C01; G01; G28; P16; 330; resilience; growth; equity; income equality; social inclusion; financial crisis; debt